On survey of Long-tailed macaque (Macaca Fascicularis) population in Central Java Province - Maharadatunkamsi Maharadatunkamsi; Margareta Rahayuningsih; Sigit Wiantoro; Eko Sulistyadi; Nurul Inayah (Indonesian Journal of Conservation, 2023)
Long-Tailed Macaque or â€œLTMâ€ (Macaca fascicularis) is one of the internationally traded species andÂ  most of the exported LTM are taken from the wild includng in Indonesia. This massive exploitation may result in extinction. Therefore, regulations to set the LTM export quota are necessary. One of the activities to set this quota is the LTM population survey. Data on LTM population in each area especially Indonesia Â is insufficient. Governments, together with stakeholders, begin to estimate the LTM population in the field include in Central Java. The objective of the study was to analyze estimation of the population on LTM in Central Java especially in nine districy/city.Survey of LTM population in Central Java is implemented in nine District/City. , i.e., Semarang District, Magelang District, Temanggung District, Pemalang District, Boyolali District, Karanganyar District, Sukoharjo District, Wonogiri District, and Semarang City. Population data obtained by using the method concentration count. The observation was repeated at least twice at each observation point. The observation units are morning and afternoon (one-time observation). The observation is carried out at 05.30-11.00 (morning) and 15.00-17.00 (afternoon). The Result of tf the research showed total of 811 LTM individuals are encountered during data collection in nineÂ  districts/cities in Central Java. Total survey area in nine districts/cities is 331.07 ha. Kreo Cave, Semarang City, is one of the locations with the highest number of LTM (164Â  individuals), and the lower number of LTM in Boyolali distric (43 individuals).